A model for an economic evaluation of energy systems using TRNSYS. (1st April 2018) - Villa-Arrieta, Manuel; Sumper, Andreas
Highlights: A new model, tool, for technical-economic evaluation of energy systems is proposed. Built in TRNSYS, the tool dynamically links technical and economic variables. The tool works in parallel to the technical evaluations of energy systems. The tool allows evaluates self-consumption and energy generation systems. The tool was validated to evaluate net-zero energy communities. Abstract: This paper presents a technical-economic model for the evaluation of energy systems called Energy Assessment Tool of Energy Projects (EATEP). It was created with the TRaNsient System Simulation Tool (TRNSYS) and works in parallel to the technical simulations in this software. The EATEP links, in hourly time steps, technical and economic variables that can determine the functioning of energy systems and the profitability of the investment required for their implementation. The economic calculation procedure, as described in the European standard EN 15459:2007, of the Energy Performance of Buildings Directive (EPBD) of the European Commission, has been adapted to the characteristics of TRNSYS to develop the calculation methodology of the EATEP. The final use of this resulting tool is the evaluation of the energy self-consumption of communities from the technical-economic point of view, analyzing the investment in distributed generation systems by consumers, prosumers and energy producers. The operation of the EATEP has been validated through two cases that demonstrate the wide range of its applicability and versatility. In the first case, the calculation of indicators identifies the best alternative among various investment options in the evaluation of self-consumption energy systems. The second case, evaluates systems in which producers, consumers and prosumers exchange energy and economic flows; the tool calculates indicators of costs, revenue and income (the margin between revenue and costs).